The Role of Legal Counsel in Customs and Excise Disputes before the Tax Court - Rudi Kurniawan; Syahrul Borman; Fathul Hamdani; Noenik Soekorini (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study aims to analyze the role of legal counsel in resolving customs and excise disputes before the Tax Court, with particular reference to Decision Number 1430/B/PK/Pjk/2026. The research focuses on how legal counsel contributes to legal argumentation, evidentiary effectiveness, and the realization of legal certainty and legal protection in customs dispute resolution. Research Methodology: This study employs a qualitative approach with a normative juridical method. The research applies statutory, conceptual, and case approaches by analyzing primary legal materials, including customs law, excise law, Tax Court law, and Constitutional Court decisions, supported by secondary legal materials from national and international scholarly journals (2019–2026). Data analysis is conducted through descriptivequalitative interpretation. Conclusions: The study concludes that the effectiveness of customs and excise dispute resolution before the Tax Court is highly dependent on the competence of legal counsel in constructing legal arguments and managing evidence. Legal counsel is essential in ensuring justice, legal certainty, and protection of parties' rights within the tax litigation system. Limitations: This study is limited to normative juridical analysis based on document review and does not include empirical data such as interviews with judges, customs officials, or legal practitioners. The scope of literature also relies primarily on national sources, with limited comparative international analysis. Contributions: This research contributes to customs and tax litigation studies by highlighting legal counsel as a strategic actor in dispute resolution, offering theoretical and practical insights to strengthen judicial quality and legal certainty in customs and excise cases.